Symbolism and Cultural Significance of Hena House in Tasik Serai Village, Bengkalis District, Riau Province - Nora, Syofia (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
This study seeks to elucidate the symbolic meanings and interpretations associated with the henna house dance performed within the village of Tasik Serai. The research methodology employed in this study adheres to a qualitative approach, specifically employing descriptive analysis. The henna house dance typically involves an odd number of dancers. The dance incorporates the symbolic attributes of shawls and bale-bales adorned with flowers and eight candles, which are arranged in a circular pattern around the bale-bale. Notably, a single candle is positioned above the top of the bale-bale. The research methodology employed in this study adheres to a qualitative approach, specifically employing descriptive analysis. The findings of this study reveal that the candles burning within the bale-bales serve as a symbolic representation of fire, embodying the inherent nature of fire as a consuming element. This symbolism is further interpreted as a protective measure, safeguarding the bride and groom from potential dangers.